Pengembangan Lembar Kerja Peserta Didik (LKPD) dengan Soal Kontekstual Ditinjau dari Kemampuan Berpikir Kritis Peserta Didik - Mai Syaroh, Veni; Mustika, Juitaning (Institut Agama Islam Negeri Curup, 2024)
This research aims to develop Student Worksheets (LKPD) that utilize contextual problems in teaching plane geometry (quadrilaterals & triangles) while considering students' critical thinking abilities. The study adopts a Research and Development (R&D) approach with the 4D development model, which includes the Define, Design, Development, and Disseminate phases. The research was conducted at SMP Negeri 1 Batanghari with a sample of 10 students from class VII.3. The research instruments used in this study include expert validation questionnaires to assess the validity of the LKPD, student response questionnaires to measure the practicality of the LKPD and six essay-type test items to measure the effectiveness of the LKPD. The research findings indicate that the developed LKPD has high quality in terms of validity. The overall average scores from material and media expert validation were 3.675 and 3.275, respectively. Furthermore, the student response questionnaire showed that the LKPD meets the practicality criteria with an overall average score of 2.95. Regarding effectiveness, the test results demonstrate that the LKPD is effective with, a learning mastery rate of 60%, which falls into the category of reasonably good.